Analisis tingkat kematangan website SIMPELIN Disdukcapil Kabupaten Sukabumi menggunakan framework COBIT 2019 - Helwa Aulia Wahyudi; Arny Lattu; Hendri Ekasatria (AITI, 2026)
The SIMPELIN website is an online service system developed by the Department of Population and Civil Registration of Sukabumi Regency to facilitate the public in managing civil administration documents digitally. Based on interviews with internal personnel responsible for managing SIMPELIN, the system still faces several challenges, including system disruptions, delays in document updates, and a lack of a comprehensive evaluation of data management. This study aims to analyze the maturity level of data management on the SIMPELIN website using the COBIT 2019 framework. The methods used include observation, interviews, the development of a RACI Chart, and capability level assessment. Data were obtained through interviews with two respondents identified based on the responsibility mapping in the RACI Chart. The results show that the data management capability level is at level 3, indicating that processes are documented but not yet consistently implemented. Based on these findings, a set of recommendations was formulated to improve the effectiveness of SIMPELIN’s service management, making it more structured, efficient, and aligned with the principles of information technology governance.